1996
DOI: 10.1172/jci118414
|View full text |Cite
|
Sign up to set email alerts
|

Role of transiently altered sarcolemmal membrane permeability and basic fibroblast growth factor release in the hypertrophic response of adult rat ventricular myocytes to increased mechanical activity in vitro.

Abstract: One of the trophic factors that has been implicated in initiating or facilitating growth in response to increased mechanical stress in several tissues and cell types is basic fibroblast growth factor (bFGF; FGF-2). Although mammalian cardiac muscle cells express bFGF, it is not known whether it plays a role in mediating cardiac adaptation to increased load, nor how release of the cytosolic 18-kD isoform of bFGF would be regulated in response to increased mechanical stress. To test the hypothesis that increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(97 citation statements)
references
References 70 publications
4
92
0
1
Order By: Relevance
“…Induction of hypertrophy in neonatal cardiac myocytes using a variety of model systems and hypertrophic stimuli is associ- (25)(26)(27)(28). Contractile stimulation of cardiac myocytes in serum-free culture results in cardiac growth and increased myofibrillar organization in vitro, suggesting that the alterations in myofibrillar content may occur by an autocrine pathway (29,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction of hypertrophy in neonatal cardiac myocytes using a variety of model systems and hypertrophic stimuli is associ- (25)(26)(27)(28). Contractile stimulation of cardiac myocytes in serum-free culture results in cardiac growth and increased myofibrillar organization in vitro, suggesting that the alterations in myofibrillar content may occur by an autocrine pathway (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which increases in the contraction rate-e.g., by long-term electrical stimulationinfluences the process of cardiac growth and differentiation is an intense area of investigation. McDonough et al (6) have suggested that regulation of atrial natriuretic factor secretion by electrically stimulated neonatal rat cardiac myocytes is primarily dependent on contractile calcium transients and calmodulin kinase, independent of protein kinase C. Release of basic fibroblast growth factor from paced myocytes into the medium has been proposed to account for the hypertrophic response in adult rat ventricular myocytes (26). Other investigators have demonstrated that mechanical stretch activates phosphorylation cascades, including protein kinase C, mitogen-activated protein kinases and p90rsk (27).…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, mechanostimulated changes in gene expression and other cell functions often depend on autocrine signaling mechanisms (21,36,50,54,66), and cell wounding can lead to release of molecules that mediate these responses (7,9,33,42). Whether the increase in c-fos mRNA levels in response to contraction of stressed collagen matrices also depends on an autocrine mechanism remains to be studied.…”
Section: Fig 10mentioning
confidence: 99%
“…The gastric mucosal bFGF levels were quanti®ed by an enzyme-linked immunosorbent assay (ELISA) measurement 18 with a bFGF ELISA kit (Wako Pure Chemical Industries Ltd, Osaka, Japan) according to the manufacturer's instructions. The mucosal samples (100 mg) were homogenized in 1 mL PBS (pH 7.4) for 30 s under ice-cold conditions, followed by centrifugation at 20 000´g for 20 min at 4°C.…”
Section: Measurement Of Bfgf Level In the Gastric Mucosamentioning
confidence: 99%